The causal association between bone mineral density and risk of osteoarthritis: A Mendelian randomization study - Jiang, Liying; Jiang, Ying; Wang, Anqi; Wu, Cui; Shen, Yi (Frontiers in Endocrinology, 2023)
Objectives: The causal direction and magnitude of the association between total body bone mineral density(TB-BMD) and osteoarthritis(OA) risk is uncertain owing to the susceptibility of observational studies to confounding and reverse causation. The study aimed to explore the relationships between TB-BMD concentration and OA using Mendelian randomization(MR). Methods: In this study, we used two-sample MR to obtain unconfounded estimates of the effect of TB-BMD on hip and knee OA. Single nucleotide polymorphisms(SNPs) strongly associated with TB-BMD in a large genome-wide association study(GWAS) were identified and selected as instrumental variables(IVs). In addition to the main analysis using inverse-variance weighted(IVW) method, we applied 2 additional methods to control for pleiotropy(MR-Egger regression, weighted median estimator) and compared the respective MR estimates. Results: MR analyses suggested that genetically predicted higher TB-BMD is associated with risks of hip OA(For IVW: OR=1.199, 95%CI: 1.02-1.42, P=0.032; for WM: OR=1.257, 95%CI: 1.09-1.45, P=0.002). There was no evidence that the observed causal effect between TB-BMD and the risk of hip OA was affected by genetic pleiotropy(P=0.618). Additionally, our study didn’t support causal effects of a genetically increased TB-BMD risk on knee OA risk(OR=1.121, 95%CI: 0.99-1.28, P=0.084 using IVW; OR=1.132, 95%CI: 0.99-1.29, P=0.068 using WM; OR=1.274, 95%CI: 0.88-1.85, P=0.217 using MR-Egger). Conclusions: Our findings support a causal effect that a genetic predisposition to systematically higher TB-BMD was associated with the risk of OA. And, TB-BMD likely exerts an effect on the risk of hip OA not knee OA.